The Exoneration Clause Harms the Buyer Legal Protection for Consumers Against the Application of Exoneration Clauses in Online Sale - Masrofah Masrofah (UMPurwokerto Law Review, 2022)
AbstractToday's society is accustomed to buying and selling transactions carried out using technology and electronic media. According to Islamic law, buying and selling online is permissible. However, in the agreement process, the seller often uses the Exoneration Clause, in which the seller delegates responsibility to the Buyer and has the potential to harm the Buyer. The formulation of the problem in this study are: (1) How is the legal protection for consumers against the application of the Exoneration Clause in online buying and selling agreements according to Islamic Law? (2) What are the steps that the Buyer can take if they are harmed by the Exoneration Clause in the online sale and purchase agreement according to Islamic Law? The research method used is normative juridical, which is a research method that focuses on examining the application of applicable legal rules and norms regarding the Exoneration Clause. The study results: Consumer protection in Islamic law is explained through the existence of Khiyar rights contained in article 20 point 8 of KHES, which means the right to vote for sellers and buyers to continue or cancel the sale and purchase contract. KHES and the Positive Law on Consumer Protection have prohibited the implementation of the Exoneration Clause in this case against the execution of online buying and selling because it has the potential to harm consumers by unilaterally transferring responsibilities, eliminating consumer rights, and placing consumers in a weak position. Efforts that can be taken if the Exoneration Clause harms the Buyer in this online sale and purchase is that the Buyer can choose the rights of Khiyar Ghabn and Taghrib, namely the Buyer can demand the supply of goods that match the description, and if there is fraud or incompatibility of interests, the Buyer can do no further. Keywords: Exoneration Clause, Online Buying and Selling, Islamic Law AbstrakMasyarakat saat ini terbiasa menggunakan transaksi jual beli yang dilakukan dengan menggunakan teknologi dan media elektronik. Menurut  hukum  Islam, praktik jual beli online adalah boleh. Namun dalam proses perjanjiannya kerapkali penjual menggunakan Klausula Eksonerasi yang mana penjual melimpahkan tanggung jawab kepada pembeli dan berpotensi merugikan pembeli. Rumusan masalah dalam penelitian ini yaitu bagaimana perlindungan hukum bagi konsumen terhadap penerapan Klausula Eksonerasi pada perjanjian jual beli online menurut Hukum Islam dan bagaimana upaya yang dapat ditempuh pembeli jika dirugikan dengan adanya Klausula Eksonerasi pada perjanjian jual beli online menurut Hukum Islam. Metode penelitian yang digunakan adalah yuridis normatif, yaitu metode penelitian yang fokus  mengkaji penerapan kaidah dan norma hukum yang berlaku mengenai Klausula Eksonerasi. Berdasarkan penelitian, diperoleh hasil bahwa perlindungan konsumen dalam Hukum Islam dijelaskan melalui adanya hak Khiyar yang terdapat pada pasal 20 poin 8 KHES yang diartikan hak pilih bagi penjual dan pembeli untuk melanjutkan atau membatalkan akad jual beli yang dilakukannya. KHES maupun Hukum Perlindungan Konsumen telah melarang pelaksanaan Klausula Eksonerasi dalam jual beli online, karena berpotensi merugikan konsumen dengan pengalihan tanggungjawab secara sepihak, menghilangkan hak-hak konsumen dan menempatkan konsumen diposisi sangat lemah. Upaya yang dapat ditempuh jika pembeli dirugikan dengan adanya Klausula Eksonerasi dalam jual beli online ini yaitu pembeli dapat memilih hak Khiyar Ghabn dan Taghrib, yaitu pembeli dapat menuntut penyediaan barang yang sesuai dengan deskripsi dan jika terjadi penipuan atau ketidaksesuaian barang maka pembeli dapat melakukan tindak lanjut.Kata kunci: Klausula Eksonerasi, Jual Beli Online, Hukum Islam